Manajemen Tenaga Kependidikan di SMP IT ULIL ALBAB Pematang Siantar - Uchrowi Nasution, Fairuza Nur; Darmansyah, Tengku (Universitas Labuhanbatu, 2022)
This study discusses the application of Education Personnel Management in SMP Islam Terpadu Ulil Albab Pematang Siantar. The research method used is quantitative research. Researchers process and analyze the data that has been obtained in the field by using Miles and Huberman analysis models and testing the validity of the data used by researchers, namely triangulation of sources, methods, and time. The results of the research that researchers have been able to in the field show that, the implementation of the management of educational personnel in SMP it Ulil Albab Pematang Siantar has been well applied in accordance with the theory of planning and analysis, then hold recruitment and selection properly, implement the introduction, placement, and dismissal in accordance with the procedures, conduct training and development, provision of compensation or Remuneration, and termination of the appropriate relationship between theory and application applied in SMP IT Ulil Albab Pematang Siantar, The performance of employees at SMP it Ulil Albab Pematang Siantar has been very good. as evidenced by the increasing number of applicants for new prospective students in each new school year and the achievements achieved by their students prove that teachers and employees at SMP it Ulil Albab Pematang Siantar have a good performance., The supporting factors for the implementation of the implementation of Education Personnel Management in SMP it Ulil Albab Pematang Siantar run successfully because employees get good attention such as the fulfillment of facilities and infrastructure to support the teaching and learning process to run effectively and efficiently, the fulfillment of employee rights, and the fulfillment of the welfare of employees. There is no considerable obstacle in the implementation of Education Personnel Management in SMP it Ulil Albab Pematang Siantar.